2014
DOI: 10.1063/1.4891813
|View full text |Cite
|
Sign up to set email alerts
|

Resonances in photoabsorption: Predissociation line shapes in the 3pπD $^1\Pi _u^+ \leftarrow X^1\Sigma _g^+$Πu+1←X1Σg+ system in H2

Abstract: The predissociation of the 3pπD¹Π(u)⁺, v ≥ 3, N = 2, and N = 3 levels of diatomic hydrogen is calculated by ab initio multichannel quantum defect theory combined with a R-matrix type approach that accounts for interfering predissociation and autoionization. The theory yields absorption line widths and shapes that are in good agreement with those observed in the high-resolution synchrotron vacuum-ultraviolet absorption spectra obtained by Dickenson et al. [J. Chem. Phys. 133, 144317 (2010)] at the DESIRS beamli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In the present work, as in previous related work, 27 the electronic quantum defect matrix is effectively reduced to a single element, µ (Λ) (R) for Λ = 0 and 1, referring to the ion core ground state X + 2 Σ + g and corresponding to ℓ = ℓ ′ = 1. Consequently, the indices Λ + and ℓ may be dropped in Eq.…”
Section: Determination Of Quantum Defectsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present work, as in previous related work, 27 the electronic quantum defect matrix is effectively reduced to a single element, µ (Λ) (R) for Λ = 0 and 1, referring to the ion core ground state X + 2 Σ + g and corresponding to ℓ = ℓ ′ = 1. Consequently, the indices Λ + and ℓ may be dropped in Eq.…”
Section: Determination Of Quantum Defectsmentioning
confidence: 98%
“…22,23,27,[33][34][35] An R-matrix type procedure is introduced in order to include dissociation channels along with the ionization channels. In a first step the integration range of the ion core vibrational wavefunctions χ(R) is limited to a finite rather small value, R c , which plays the role of the vibrational core boundary in addition to the electronic core boundary r c which appears in Eq.…”
Section: E Inclusion Of Dissociation Channels In the Mqdt Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed profile is usually a convolution of the predissociation, Doppler and instrumental profiles. While the predissociation profile is normally represented by the Fano line shape formula, Mezei et al (2014) has suggested that the formula cannot accurately represent the resonant profile for the v6 levels of H 2 . Each Fano profile is described by its center frequency, width (Γ) and asymmetry (q) parameters.…”
Section: Umentioning
confidence: 99%
“…The D u 1 P + -B u 1 S + coupling is at least another order of magnitude weaker than the D u 1 P + -C u 1 P + coupling. The MQDT method, in principle, automatically includes the interaction of the D u 1 P + state with other npσ and npπ Rydberg states (Glass-Maujean et al 2012c as well as the interference between predissociation and autoionization (Mezei et al 2014). However, all investigations have confirmed that the predissociation of the D u 1 P + state is dominated by the B¢ u 1 S + continuum.…”
Section: Introductionmentioning
confidence: 99%